Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd010078
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for promoting smoking cessation during pregnancy

Abstract: Background Smoking in pregnancy is a public health problem. When used by non-pregnant smokers, pharmacotherapies (nicotine replacement therapy (NRT), bupropion and varenicline) are effective for smoking cessation, however, their efficacy and safety in pregnancy remains unknown. Electronic Nicotine Delivery Systems (ENDS), or e-cigarettes, are becoming widely used but their efficacy and safety when used for smoking cessation in pregnancy are also unknown. Objectives To determine the efficacy and safety of smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 109 publications
0
96
1
1
Order By: Relevance
“…High intensity behavioural interventions delivered by specifically trained health professionals in combination with higher doses of NRT may be required to bring about abstinence in some pregnant women with high nicotine dependence. 18 Coleman et al 19 showed that NRT was not efficacious for smoking cessation during pregnancy, but adherence to therapy was low in their study. However, a recent meta-analysis showed that pharmacotherapy (NRT, bupropion) for smoking cessation among pregnant smokers yielded a significantly greater abstinence rate, about 1.8 times higher than in the control group; overall, pharmacotherapy did not affect birth outcomes and was generally safe.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…High intensity behavioural interventions delivered by specifically trained health professionals in combination with higher doses of NRT may be required to bring about abstinence in some pregnant women with high nicotine dependence. 18 Coleman et al 19 showed that NRT was not efficacious for smoking cessation during pregnancy, but adherence to therapy was low in their study. However, a recent meta-analysis showed that pharmacotherapy (NRT, bupropion) for smoking cessation among pregnant smokers yielded a significantly greater abstinence rate, about 1.8 times higher than in the control group; overall, pharmacotherapy did not affect birth outcomes and was generally safe.…”
Section: Discussionmentioning
confidence: 91%
“…20 A Cochrane review of the efficacy and safety of smoking cessation pharmacotherapies, including NRT, varenicline and bupropion when used to support smoking cessation in pregnancy concluded that further research evidence of efficacy and safety is needed, ideally from placebo-controlled RCTs that investigate higher doses of NRT than were tested in the included studies. 18 The Association of Women's Health, Obstetric & Neonatal Nurses (AWHONN) has developed an evidence-based clinical practice programme, the Setting Universal Cessation Counselling Education and Screening Standards (SUCCESS) program, to better educate practitioners about smoking cessation. 21 Many Australian hospitals have local protocols for offering smoking cessation advice to their patients and staff; however, there is no information on the extent to which these protocols are followed by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Pragmatism has required that pharmacotherapeutic clinical trials exclude pregnant women from enrollment. This trend has recently changed, and the forward-looking focus on trials of pharmacotherapies during pregnancy is encouraging (127). Future trials should be undertaken with risk-benefit valuations made under assumptions that include the global risks of in utero smoke exposure, including those that may be incurred decades after birth.…”
Section: What We Need To Knowmentioning
confidence: 99%
“…A recent Cochrane review determined that there is as yet insufficient evidence that NRT is effective or safe in pregnancy (Coleman, Chamberlain, Davey, Cooper & Leonardi-Bee, 2012), but the review reported there were no statistically significant adverse foetal outcomes when comparing NRT to controls. Experts however have concluded that using NRT is generally safer than smoking in pregnancy (Bittoun, 2010;Forinash, Pitlick, Clark & Alstat, 2010).…”
Section: Introductionmentioning
confidence: 99%